Quality of Life of Elderly with Hypertension in Coastal Areas - Fitri, Aminatul; Agrina, Agrina; Arneliwati, Arneliwati; Sabrian, Febriana; Zulfitri, Reni (Institute Of Computer Science (IOCS), 2025)
Introduction: The prevalence of hypertension in the elderly is increasing and it can affect the quality of life of the elderly. The purpose of the study was to obtain a description of the quality of life of elderly people with hypertension in coastal areas. Methods: This study used descriptive quantitative with a sample size of 100 elderly people with hypertension in the Umban Sari health center working area. The measuring instrument used is the WHsOQOL-BREF quality of life questionnaire. The data is processed and grouped and analyzed. The data will be presented in the form of a frequency distribution. Results: The results of this study indicate that the elderly are in pre-hypertension, grade 1 hypertension and the quality of life of the elderly is 100% high. The description of the quality of life of the elderly found that 65 respondents (65%) experienced satisfaction in getting along, 65 respondents (65%) very often felt meaningful life, 46 respondents (46%) for opportunities for fun or recreation in moderation and 64 respondents (64%) said they rarely experienced uncomfortable feelings such as loneliness, despair, anxiety, sadness and moodiness. There were 59 respondents (59%) who did not take medical drugs and 79 respondents (79%) did not take herbal drugs and 96 respondents (96%) lived with their families. 95% of the elderly have never had a stroke and do not experience movement limitations. Conclusion: The quality of life of elderly people with hypertension who live in coastal areas is good